Kepemimpinan Pengasuh Perempuan di Lingkungan Sosial Pesantren: Studi atas Kepemimpinan Pengasuh Perempuan PP Manbaul Khoiriyatil Islamiyah (MHI) Jember - Eva Maghfiroh (PSGA Institut Agama Islam Tarbiyatut Tholabah, 2024)
In line with the emancipation movement and gender equality movement which essentially seeks to demand equal rights for women in various areas of life, then step by step there has been a shift in the perception of women. They are no longer seen as weak figures who are always in the back line, but they can appear at the forefront as successful leaders in various sectors of life. The purpose of this study is to describe the leadership of Nyai Sayyidah in the social environment of Islamic boarding schools. Using a descriptive qualitative method. The results of the study show that the leadership of women in Islamic boarding schools is currently able to carry out ideal leadership patterns in leading in Islamic boarding schools and carrying out activities in the Islamic boarding school environment